Pendampingan Kader Catin dalam Penjaringan Calon Pengantin di Kabupaten Jembrana - Daryaswanti, Putu Intan; Widayati, Kurniasih; Noviyanti, Ni Putu Ayu Wulan; Dewi, Ni Luh Made Asri; Febianingsih, Ni Putu Eka; Astutik, Windu; Sulistyadewi, Ni Putu Eny (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Many factors cause stunting, one of which is health problems for young women (mothers-to-be) who are about to become pregnant. In several studies, smoking behavior and exposure to cigarette smoke also have an impact on pregnancy and fetal disorders which result in stunted babies being born. Before becoming pregnant, young women must really prepare their health. This preparation can start when you reach puberty until you are ready to become a prospective bride. The female bride-to-be (catin) is a woman of childbearing age who was in a healthy condition before becoming pregnant so that she can give birth to a normal and healthy baby and the male prospective bride-to-be will be introduced to the reproductive health problems of herself and the partner she will marry. Purpose: The aim of this activity is to help cadres in recruiting catin. Method: This service activity uses counseling and discussion methods for 30 cadres of prospective brides and grooms consisting of the Traditional Village Council, Village Kelian, Village Perbekel, Village PLKB, Village TPPS, and Village Midwife Element TPK. Results: There was an increase in post test scores after being given the material. The mean pre-test score was 68 and rose to 70. There was agreement in selecting potential brides, especially Hindu brides. This flow will be disseminated to each village, and will be socialized at every meeting with teenagers. So that teenagers who will later get married go through this flow. Conclusion: The importance of health screening for prospective brides and grooms to prevent stunting in children in the future. The catin flow is a tool to make it easier to disseminate information about how prospective brides and grooms, especially Hindus, report to Kelian Desa about their wedding plans.